THE ROLE OF READING SHORT STORIES FOR ENGLISH LEARNERS - Olimjonova Shakhnoza Bakhtiyorovna (World Scientific Research Journal, 2025)
Abstract: This article explores the role of reading English stories in the language learning process. In recent years, there has been an increased focus on methods for teaching foreign languages, and reading literary works has gained importance as a vital component of educational programs. The article examines not only the advantages of reading stories, such as vocabulary expansion, improvement of grammatical skills, and enhancement of cognitive abilities, but also the psychological aspects that contribute to student motivation. We analyze various approaches to integrating reading into the educational process and present the results of an empirical study conducted with student participants. Our analysis reveals that reading English stories positively influences student engagement and helps them better understand the cultural contexts of the language. Our work offers recommendations for educators on the effective use of literary works for teaching purposes, emphasizing the importance of selecting materials that align with students' interests.